OC-041 Reduced Hospital Admission And Rapid Access To Specialist Services Through The Introduction Of A Gastroenterology And Hepatology Ambulatory Care Service. (9th June 2014) - Fielding, J; Hawley, A; Hardcastle, S; Drew, K; Gleeson, D; Karajeh, M; Sanders, D; Hopper, A; Sidhu, R; McAlindon, M; Lobo, AJ
Abstract : Introduction: Ambulatory care sensitive conditions are those where intervention may limit hospital admissions. Improvements in the management of these conditions may save the NHS £96–£238 million per annum and alleviate pressures on Accident and Emergency. This is directly applicable in Gastroenterology but few gastrointestinal (GI) conditions are conventionally listed as suitable for this approach. This study examined the effect of such a service providing rapid access to specialist services in a UK Gastroenterology Unit. Methods: A Gastroenterology ambulatory care service was established as part of an investigation unit with on-ward endoscopy facilities. General practitioners (GPs) were given written guidelines and referred to a senior nurse via telephone. Patients considered suitable were those requiring urgent assessment but where admission might be avoided. Exclusion criteria: hypotension, suspected acute abdomen, or GP concern about potential for deterioration. Results: 224 patients were referred by their GP from June 2011 to January 2013. 12 did not attend. Presentation and outcome are described in Table 1 . 179 patients (84%) were seen on arrival by a consultant. 96 patients (45%) were admitted; 116 were discharged on the same day – of whom 94 (91%) were offered either same day (n = 67 (58%)) or outpatient (n = 27 (23%)) investigations. 30 day readmission rate was only 4% (n = 5). 51 patients had low risk GI bleeds (Rockall score 0–1). 30 (59%) of these were discharged the same day and 90% (n = 27) had an OGD within 24 h of assessment, either same day or returning the following morning. Conclusion: The Ambulatory Care Service provides direct, rapid access to specialist opinion and investigation for a range of GI presentations, avoiding hospital admission for the majority referred. In contrast to other UK studies those with low risk GI bleeding were managed as out-patients but with gastroscopy undertaken. This is a model for a tiered approach to emergency care in Gastroenterology. Disclosure of Interest: None Declared.